A minimalistic, synthetic cell-inspired metamaterial for enabling reversible strain-stiffening [data] - Taale, Mohammadreza (Universität, 2024)
Strain-stiffening, i.e. the nonlinear stiffening of a material in response to a strain, is an intrinsic feature of many biological systems, including skin, blood vessels, and single cells. To avoid a mismatch in mechanical properties, synthetic materials in contact with such biological systems should also be strain-stiffening. Conventional strain-stiffening materials are either highly dependent on the applied strain-rate, or only available for a limited stiffness regime. Both aspects limit the applicability of these materials. In contrast, living cells employ a dynamic strain-stiffening mechanism that is based on the cross-linking of cytoskeletal fibers in response to external stress. This strain-stiffening of the cytoskeleton is mimicked in a mechanical metamaterial by a minimalistic structure consisting of parallel slats connected to backbones. Herein, it is demonstrated experimentally that the structures can be adapted such that the strain required for stiffening, the final stiffness, as well as the degree of stiffening can be tuned, particularly by combining several strain-stiffening elements. These properties make the structure promising for the development of devices that should resemble the mechanical properties of human soft tissues, e.g., skin-integrated flexible electronics and blood vessel grafts.
Finanziert durch: European Research Council: VASCUGRAFT, no. 899701; BMBF; DFG: 2082/1-390761711; Carl Zeiss Foundation; Volkswagen Foundation
Gesehen am 21.02.2024
Keywords: Forschungsdaten; Datenbank